Global Faulkner : Faulkner and Yoknapatawpha, 2006 - Trefzer, Annette, 1960-; Abadie, Ann J. (Faulkner and Yoknapatawpha., 2009)
Today, debates about globalization raise both hopes and fears. But what about during William Faulkner?s time? Was he aware of worldwide cultural, historical, and economic developments? Just how interested was Faulkner in the global scheme of things?. The contributors to Global Faulkner suggest that a global context is helpful for recognizing the broader international meanings of Faulkner?s celebrated regional landscape. Several scholars address how the flow of capital from the time of slavery through the Cold War period in his fiction links Faulkner?s South with the larger world. Other authors.